Comparison between Ransons score and modified CTSI in predicting the severity of acute pancreatitis based on modified Atlanta classification 2012 - B. D., Manjunath; Ali, Mohammed Arafath; Razack, Abdul; H. R., Harindranath; K., Avinash; T., Kavya; Vijayakumar, Lakshmi (International Surgery Journal, 2019)
Background: Acute pancreatitis is an inflammatory process of the pancreas with possible peripancreatic tissue and multiorgan involvement inducing multiorgan dysfunction syndrome (MODS) with a high mortality rateand hence early identification of patients at risk for severe disease is of vital importance. Methods: Data were collected from 50 patients who presented to the emergency department of hospitals attached to BMCRI, Bangalore, having acute pancreatitis. Results: The study included 50 patients- 40 males and 10 females and median patient age was 54.5years.Out of the 50 patients, 40% had gall stones, 56% were alcoholic and 4% had idiopathic pancreatitis.56% were found to have a Ransons score of >3 and 44% had score < 3; 52%had a modified CTSI score of 0-2, 52%had a score of 4-6 and 22% had a score of 8-10. The incidence of severe acute pancreatitis in patients with Ransons score >3 has a p value <0.002. Also, the incidence of severe acute pancreatitis in patients with modified CTSI score >4 has a p value of <0.001.With respect to mortality, all 4 patients who died had a modified CTSI score of >4 (p=0.002) and 3 patients had Ransons score >3 (p=0.03) which is statistically significant. Conclusions: In our country where facility for CECT is not available to a major proportion of population, early assessment of severe pancreatitis can be performed by Ransons scoring, which is found to be comparable to modified CTSI scoring.